2015
DOI: 10.1007/s12571-015-0467-4
|View full text |Cite
|
Sign up to set email alerts
|

The short-term impact of price shocks on food security-Evidence from urban and rural Ethiopia

Abstract: This study investigates the impact of food price changes on food security in urban and rural Ethiopia. Using a quarterly household survey panel dataset and price data collected directly at markets, a negative effect of high cereal prices on some, but not all considered indicators of food security was found, controlling for unobserved heterogeneity across households. The results indicate that increases in cereal prices are generally, but not always, associated with households having a lower number of meals and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 20 publications
0
24
0
2
Order By: Relevance
“…Literature on nutrition (e.g., Hatloy et al 1998;Kant 2004;Matz et al 2015) shows that consumption of diverse diet has positive impact on health and thus diet diversity is a good indicator of diet quality and household food and nutritional security. Hoddinott (1999) offers a comprehensive overview of frameworks for measuring household diet diversity and food security.…”
Section: Measuring Diet Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Literature on nutrition (e.g., Hatloy et al 1998;Kant 2004;Matz et al 2015) shows that consumption of diverse diet has positive impact on health and thus diet diversity is a good indicator of diet quality and household food and nutritional security. Hoddinott (1999) offers a comprehensive overview of frameworks for measuring household diet diversity and food security.…”
Section: Measuring Diet Diversitymentioning
confidence: 99%
“…We focus on the diet quality aspect of food security of Roma and reveal possible cultural (institutional) and economic (marginalisation) forces determining their choices of diet. In the nutrition economics literature (e.g., Fernandez et al 1996;Hatloy et al 1998;Arimond and Ruel 2004;Kant 2004;Matz et al 2015) and food economics literature (e.g., Theil and Finke 1983;Jackson 1984;Thiele and Weiss 2003;Herzfeld et al 2014;Braha et al 2017) diet diversity is commonly employed as a proxy for diet quality. 2 It is established that consumption of a diverse diet has a positive impact on health and that diet diversity is a good indicator of food security at the household level.…”
Section: Introductionmentioning
confidence: 99%
“…As non-meat consumption has become more widespread it has also more clearly become a middle-class phenomenon. Matz et al (2015) study investigated the impact of food price changes on food security in urban and rural Ethiopia. The results indicated that increases in cereal prices are generally, but not always, associated with households having a lower number of meals and switching to less preferred foods.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Sebaliknya, rumah tangga yang memiliki pendapatan rendah hanya akan mengonsumsi produk pangan tertentu saja, terutama komoditas beras. Selain itu, faktor harga pangan memengaruhi permintaan rumah tangga terhadap jenis pangan tertentu, yang kemudian akan memengaruhi permintaan efektif/konsumsi pangan rumah tangga (Torlesse et al 2003;Matz et al 2015). Tinggi atau rendahnya tingkat diversifikasi pangan rumah tangga ditunjukkan oleh pola konsumsinya.…”
Section: Kerangka Pemikiranunclassified